The Impact of COVID-19 on Small-Scale Sporting Events in South Africa - Ayanda J. MCHUNU; Siyabulela NYIKANA; Tembi M. TICHAAWA (Editura Universităţii din Oradea, 2022)
This article evaluates the impact that COVID-19 has had on small-scale sporting events within the context of South Africa. To this end, it considers the impacts that the pandemic has had on these types of events, and reflects on the strategic direction in the management and organisation of these events going forward. To achieve this, a content analysis of existing frameworks and documentary analysis of government policies and strategies, coupled with interviews with stakeholders involved in the organisation and management of small-scale sporting events domain was conducted. Through a purposive sampling technique, as well as snowballing, key stakeholders in the small-scale sporting event domain were interviewed using a semi-structured interview schedule. The key findings revealed that small-scale sport events experienced great financial loss due to the global pandemic which resulted in some of these events having to cease their operations during the hard lockdown levels. However, the lessons learnt during these times have offered event organisers ideas and guidelines for dealing with future external shocks. A key observation is made for increased governmental support for small-scale sporting events in this regard. This research forms a basis for improved understanding of sport tourism, and specifically smallscale events especially in changing times.